Fetal Congenital Complete Heart Block: A Rare Case with an Extremely Low Ventricular Rate and Review of Current Management Strategies - Stefani Samples; Catherine Fitt; Michael Satzer; Ronald Wakai; Janette Strasburger; Sheetal Patel (MDPI AG, 2023)
Congenital complete heart block (CCHB) is associated with high intrauterine and post-natal mortality. Prenatal detection and management, as well as appropriate delivery planning, may improve the outcomes in CCHB. We describe a rare case of CCHB that initially presented with fetal ascites and high-grade second-degree heart block noted on fetal echocardiography. The mother was noted to be positive for anti-SSA antibodies, and treatment with maternal steroids was started in an effort to reverse the fetal cardiac conduction abnormality. However, the fetal cardiac rhythm progressed to complete heart block by the follow up evaluation and the fetus had a continual declination of heart rate throughout the pregnancy to a low fetal heart rate of 25 beats per minute (bpm). This case demonstrates the lowest fetal ventricular rate documented in the literature and illustrates a severe presentation of a rare disease process. An overview of the existing knowledge related to etiology, prenatal evaluation with fetal echocardiography and fetal magnetocardiography, prenatal management, and delivery planning in fetuses with prenatally detected CCHB is included.